Instrumental Music Educators in a COVID Landscape: A Reassertion of Relationality and Connection in Teaching Practice - de Bruin, Leon R. (Frontiers in Psychology, 2021)
For many countries instrumental music tuition in secondary schools is a ubiquitous event that provides situated and personalised instruction in the learning of an instrument. Opportunities and methods through which teachers operate during the COVID-19 outbreak challenged music educators as to how they taught, engaged and interacted with students across online platforms, with alarm over aerosol dispersement a major factor in maintaining online instrumental music tuition even as students returned to ‘normal’ face to face classes.This qualitative study investigated the practices employed by instrumental music educators in secondary schools in Melbourne, Australia, analysing teacher perspectives to music tuition amidst the restriction of interaction with students remotely via online means. Thematic analysis of the interview transcripts revealed music educational approaches that fostered connection, empathy and receptiveness to relationship-building, guiding students in slower and deeper learner-centred approaches, asserting pedagogical practices that reinforced and promoted interpersonal connectedness in and through musical experience and discovery. These findings provide a framework for how music educators can facilitate connection, motivation and student autonomy generating personal meaning and commitment to music making and the learning relationship, which can translate to significant student learning and value in the learning music. Exploring teachers’ pedagogical practices and behaviours within this dyadic teacher-student relationship is a significant addition to the literature, enabling the consideration of the type of connective behaviours required to stimulate and develop long-term interest in music.